Student Reports and Faculty Perceptions of Academic Dishonesty - Kidwell, Linda Achey (Teaching business ethics, 2003)
As college students prepare for the businessworld, what they learn as acceptable behavioron campus may well inform their expectations ofacceptable behavior in their professionallives. Numerous studies have reported thatmost college students admit to cheating onmultiple occasions (e.g., McCabe and Trevino,1993; Sims, 1993; McCabe, Trevino andButterfield, 1996, 1999). Furthermore,studies have linked academic integrity withethical business practices (McCabe, Trevinoand Butterfield, 1996; Sims, 1993). Oneapproach to reducing academic dishonesty hasbeen the student honor code. Such codes havebeen on the rise for the last decade (Pavelaand McCabe, 1993). Honor codes have been usedas a teaching tool to underscore the importanceof professional ethics among business students(Kidwell, 2001)., In the effort to establish a culture ofacademic integrity, a university must firstunderstand the current state. This paperdiscusses a two-year study at a small liberalarts university without an honor code at thepresent time. Students were surveyed abouttheir cheating behaviors as well as theirreceptiveness to an honor code. Over seventypercent of the students surveyed reported thatthey were habitual cheaters, i.e., they hadcheated on exams, plagiarized papers, orcommitted other forms of academic dishonesty onmultiple occasions. A survey similar to thatadministered to students was subsequentlyadministered to faculty in order to determinetheir understanding of student cheating norms. This paper compares the student and facultyperceptions, and the prospects for an honorcode at the university are also explored.